Development and Validation of the Intimate Partner Sexual Violence Scale (IPSVS): A Multi-Dimensional Scale to Measure Sexual Violence in Intimate Relationships - Tarzia, Laura (Journal of interpersonal violence, 2025)
Intimate partner sexual violence (IPSV) is defined as any non-consensual sexual behavior perpetrated within an intimate relationship. It is overwhelmingly perpetrated by men against women and causes significant harm to the health and wellbeing of victim/survivors. Although it is generally accepted that IPSV is globally prevalent, to date, comprehensive instruments to measure IPSV have been lacking. Moreover, existing measurement tools have largely failed to capture the diversity of perpetrator tactics, the deeply degrading and dehumanizing nature of many IPSV behaviors, and the role of perpetrator intent. As a result, there is a dearth of robust quantitative data to help understand the nature and magnitude of the problem. This article describes the development of a new multi-dimensional measurement tool—the Intimate Partner Sexual Violence Scale (IPSVS). The IPSVS is grounded in qualitative evidence from victim/survivors and examines IPSV as a multi-dimensional phenomenon with perpetrator intent as a central organizing principle. Following consultation with experts, a representative sample of 702 women victim/survivors in Australia completed an online survey including 34 IPSV behaviors to establish reliability and validity of the items. Exploratory factor analysis revealed 20 items across 3 factors—“Dominance and humiliation,” “Emotional coercion,” and “Aggressive indifference”—explaining 52.681% of the variance. Cronbach’s alphas ranged from .741 to .890. These domains highlight that different perpetrator motivations may underlie different types of IPSV, challenging the predominant classification of IPSV according to severity or level of physical harm. The IPSVS has the potential to dramatically improve measurement of sexual violence in intimate relationships and has important implications for future research and practice.